HOW TO TRANSFORMATIONAL LEADERSHIP INCREASE EMPLOYEE PERFORMANCE: (STUDY CASE: PT. RISKY LINTAS SAMUDERA) - Mayumi Risky Ramadhani; Liliana Dewi (Media Mahardhika, 2021)
The business world does not always go by what everyone wants. Business in any sector will always experience ups and downs, depending on what underlies a business experiences both of these. This research was conducted with the aim to find out: (1) the influence of transformational leadership style on the performance of the employees of PT. Risky Lintas Samudera (2) the effect of employee empowerment on the performance of employees of PT. Risky Lintas Samudera. PT. Risky Lintas Samudera is a company engaged in freight forwarding expedition services with domicile in Surabaya. This study uses quantitative methods. Data collection was carried out, by distributing questionnaires to 40 employees of PT. Risky Lintas Samudera. Testing in this study uses the Partial Least Square (PLS) analysis technique. The results of this study are two findings, namely: (1) The relationship between the influence of transformational leadership style on employee performance has a T-statistic value> 1.96 of 10,451 so that the first hypothesis can be accepted. The first hypothesis can be said that the transformational leadership style has a significant influence on the performance of employees of PT. Risky Lintas Samudera. (2) The relationship between Employee Empowerment and employee performance has a T-Statistic value of <1.96 of 0.216 so that the second hypothesis cannot be accepted. The second hypothesis can be said to have no significant effect on the performance of employees of PT. Risky Lintas Samudera.